Struktur Naratif Legenda Candi Pari dan Candi Sumur di Kecamatan Porong Kabupaten Sidoarjo - Mifta Khuljannah; Sucipto Sucipto; Boedi Martono (LP4MK STKIP PGRI Lubuklinggau, 2020)
One culture that is still inherent in society is oral literature. Oral literature existed before the public recognized written literature, but its existence is difficult to preserve because it depends on the speaker. In this connection, the researcher was interested and wanted to explore the narrative structure of the Pari and Sumur Temples in Porong District, Sidoarjo Regency. The theory used in this research was Maranda's narrative analysis theory and Kasim's comparative literature. The method used is descriptive qualitative because the data analyzed in the form of words or sentences. Data sources came from in-depth interviews with several informants. Data collection techniques used by researchers are observation, interviews, recording, recording, documentation, transcript techniques, and transliteration techniques. To obtain valid data, researchers used source triangulation by comparing information obtained from several different informants. The results of this study indicate that there is a linkage between the term narrative structure and function in the legend of Pari Temple and Sumur Temple. The most prominent characteristic between the two temples is that the Pari Temple is always synonymous with places of worship for Hindus, while the Sumur Temple is used as a place to take water to purify oneself before worshiping at Pari Temple.